Ribozymes, riboswitches and beyond: regulation of gene expression without proteins - Serganov, Alexander (Nat Rev Genet, 2007)
Although various functions of RNA are carried out in conjunction with proteins, some catalytic RNAs, or ribozymes, which contribute to a range of cellular processes, require little or no assistance from proteins. Furthermore, the discovery of metabolite-sensing riboswitches and other types of RNA sensors has revealed RNA-based mechanisms that cells use to regulate gene expression in response to internal and external changes. Structural studies have shown how these RNAs can carry out a range of functions. In addition, the contribution of ribozymes and riboswitches to gene expression is being revealed as far more widespread than was previously appreciated. These findings have implications for understanding how cellular functions might have evolved from RNA-based origins.